Effects of 17?-estradiol injection on the reproductive efficiency of freshwater crayfish, Astacus leptodactylus (Eschscholtz, 1823) - Harlıoğlu, Muzaffer Mustafa; Yonar, Muhammet Enis; Harlıoğlu, Ayşe Gül; Yonar, Serpil Mişe; Farhadi, Ardavan (Taylor and Francis Inc., 2018)
The effects of 17?-estradiol injection (10?7mol/crayfish) in adult female Astacus leptodactylus on the reproductive efficiency (i.e., pleopodal egg and stage 1 juvenile numbers) were investigated. In addition, hepatosomatic index, gonodosomatic index, and 17?-estradiol (E2) levels of crayfish ovary, hepatopancreas, and heamolymph before and after injections were also determined. Results showed that E2 injection to females enhances the reproductive efficiency of A.leptodctylus. E2 injection significantly increased pleopodal egg and stage 1 juvenile numbers, GSI, HSI, and concentrations of E2 in heamolymph, ovary, and hepatopancreas. However, E2 injection did not accelerate time of mating and proportion of pleopodal egg-berried females at the first week of reproduction season in this species. This study highlights that to improve the reproductive efficiency of A.leptodctylus by using hormones to regulate the ovarian cycle, E2 should be used at least 1.5 months before the commencement of the breeding season. © 2018, © 2018 Taylor & Francis.
Keywords: female crayfish; hormone; physiology; Reproduction